From Isolationism to Interventionism. Book Review of ‘The U.S.-German Relations, 1938–1941: Politics, Diplomacy, Priorities’ by O.V. Petrosyants - D. V. Rodin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The book under review is a monograph by O.V. Petrosyants ‘The U.S.-German relations, 1938–1941: Politics, diplomacy, priorities’ published in 2021. The reviewer emphasizes the relevance and novelty of the research as it revisits a set of well-established in both the Soviet and Russian historical studies views on and assessments of the U.S. foreign policy before and at the beginning of World War II. The monograph is based on a wide range of primary sources including previously unpublished documents from the Russian and American archives. It reveals a complex and contradictory nature of the U.S. foreign policy at the turn of the 1930s and 1940s and identifies its key internal and external determinants. The reviewer notes that the study pays special attention to tensions between isolationists and interventionists within the American elites and agrees with the author’s conclusion that the isolationists’ position turned out to be more and more regressive and short-sighted as the international situation worsened. However, as the author emphasizes, it was the need to take into account the isolationists’ influence that largely led to the inconsistency and indecisiveness of the U.S. foreign policy during that period. The reviewer stresses that such balanced assessments characterize all the chapters of the book which makes it a must-read for all specialists on the U.S. foreign policy. However, the reviewer notes that the German diplomacy is not examined in the book as consistently and thoroughly as that of Washington and often appears as a mere observer. The reviewer concludes that this research is especially relevant and worthy of attention in the current international context since it points to the need for an objective and unbiased study of the foreign policy of past and present Russia’s rivals as a key to a better understanding of their current goals.